Evaluation of iron-folic acid supplementation in young women in Mataram City - Eka Suci Kantari; Emy Huriyati; Mirza Hapsari Sakti Titis Penggalih (Berita Kedokteran Masyarakat, 2022)
Purpose: The government program to prevent iron deficiency anemia in adolescent girls provides iron-folic acid supplementation, usually known as TTD or "Tablet Tambah Darah". The number of adolescent girls who received TTD was 76.2%, whereas 80.9% were given at school, and the rest were from other sources. The obedience of young women to consuming TTD is one factor that affects the effectiveness of the TTD program.Methods: This research was a cross-sectional study of a non-experimental design survey. The study sample was 159 people, 15-to 18-year-old adolescent girls of SMAN 5 Mataram. Results: Bivariate analysis showed that attitudes and obstacles were not statistically related to compliance, as seen from the attitude value p-value = 0.052 and resistance p-value 0.135. Obstacles have a relationship with attitudes with a value of p = 0.01. Conclusion: Attitudes and obstacles have no relationship to obedience in adolescent girls, while obstacles have a relationship with attitudes towards adolescent girls.